Prediction of Immune-Checkpoint Blockade Monotherapy Response in Patients With Melanoma Based on Easily Accessible Clinical Indicators - Byun, Hwa Kyung; Chang, Jee Suk; Jung, Minkyu; Koom, Woong Sub; Chung, Kee Yang; Oh, Byung Ho; Roh, Mi Ryung; Kim, Kyung Hwan; Lee, Choong-Kun; Shin, Sang Joon (Frontiers in Oncology, 2021)
Background Immune checkpoint blocker (ICB) has shown significant clinical activity in melanoma. However, there are no clinically approved biomarkers to aid patient selection. We aimed to identify patients with advanced or metastatic melanoma who are likely to benefit from ICB monotherapy using easily accessible clinical indicators. Materials and Methods We retrospectively reviewed the records of 134 patients with advanced or metastatic melanoma who received ICB monotherapy between 2014 and 2018. Prognostic factors of overall survival (OS) and progression-free survival (PFS) were determined using Cox regression analysis. Results During the median follow-up of 13.7 months, the median OS and PFS were 18.4 and 3.4 months, respectively. Visceral/central nervous system (CNS) metastasis (OS: adjusted hazards ratio [HR], 1.82; p=.014; PFS: HR, 1.59; p=.024), lymphopenia (<1000 cells/µL) within 3 months (OS: HR, 1.89, p=.006; PFS: HR, 1.70; p=.010), and elevated baseline lactate dehydrogenase (LDH) level (OS: HR, 2.61; p<.001; PFS: HR, 2.66; p<.001) were independent prognostic factors for both poor OS and PFS. Development of immune-related adverse events (irAE; e.g., hypothyroidism or vitiligo) within 6 months showed a trend toward better OS in multivariable analysis (HR, 0.37; p=.058). Patients with normal LDH levels and no visceral/CNS metastasis had a substantially better OS than the others (median, 40.4 vs. 13.6 months; p<.001). Among others, patients who developed irAE within 6 months achieved long-term OS (median, 43.6 vs. 13.1 months; p=.008). A decision tree was suggested using four risk factors, and the risk stratification provided significant distinction between the survival curves. Conclusion The four easily accessible clinical indicators associated with better treatment outcomes after ICB monotherapy in patients with advanced or metastatic melanoma were LDH level, the extent of disease, lymphopenia, and irAE. The combined use of these indicators can be clinically useful in improving risk stratification of patients treated with ICB monotherapy.